O aporte da comunidade escolar à coleta diferenciada de resíduos sólidos domiciliares - Domingues, Max Maciel de Oliveira e (2005)
This research introduced the concept and practice of composting to a school community. It represents a possible option of diverting a considerable amount of organic residues from the Municipal Landfill. At a test community in Araguari, the Escola Estadual Antônio Nunes de Carvalho Filho, a composting experience was planned and executed using biodegradable waste from the school kitchen and also from students´ homes and some commercial donators located in the school s neighborhood. This experience is part of the study of a new system of household waste management in the City of Araguari that is being implemented by the Municipal Department of the Environment. The research, from the introduction of the topic, through obtaining students acceptance and participation, all the way to the production of two batches of compost, took eight months. An excellent quality compost was obtained, which will be used in the school garden and in the creation of a new tree nursery at the school. Attending to one research objective, the composting practice is now being considered as candidate to integrate the course schedule. It is expected that the school community multiplies its knowledge to the citizens who directly or indirectly interact with it. The first experience of this multiplication has already occurred. As part of this project the students of the test school, upon invitation, presented their results to the community of another school, Escola Centro Educacional Municipal Mário da Silva Pereira. After this knowledge multiplication, it will be easier to convey the concept of divided collection of solid waste to all the residences of Araguari in the near future. To have a sustainable future it is essential to change the attitudes of people towards solid waste, and the present project has provided a means to do just that.